2021
DOI: 10.3390/d13050192
|View full text |Cite
|
Sign up to set email alerts
|

Mining Sorghum Biodiversity—Potential of Dual-Purpose Hybrids for Bio-Economy

Abstract: Sweet, grain, and dual-purpose sorghums differ in a number of important traits, including biomass production, total solutes in the stem juice, and sugar accumulation across the stem. Ten dual-purpose hybrids, two sweet genotypes, and two grain landraces of sorghums were characterized under temperate environmental conditions to determine their potential for bioethanol production. Five sorghum hybrids (Ganymed, Hannibal, Tarzan, Merlin, and Zerberus) performed better with respect to cane yield, juice yield, pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 62 publications
1
10
0
Order By: Relevance
“…It is mandatory, therefore, to comprehend how plants respond to P i starvation during the vegetative growth stage, and to design strategies to breed varieties with better P i uptake and use efficiency. For the current study, we took advantage of the morpho-physiological and molecular differences between a sweet (Della) and a grain (Razinieh) variety of sorghum [26][27][28][29], in order to understand how different sorghum types respond to P i starvation. We analysed morpho-physiological parameters, expression of key genes, and chemical speciation of phosphorous.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is mandatory, therefore, to comprehend how plants respond to P i starvation during the vegetative growth stage, and to design strategies to breed varieties with better P i uptake and use efficiency. For the current study, we took advantage of the morpho-physiological and molecular differences between a sweet (Della) and a grain (Razinieh) variety of sorghum [26][27][28][29], in order to understand how different sorghum types respond to P i starvation. We analysed morpho-physiological parameters, expression of key genes, and chemical speciation of phosphorous.…”
Section: Resultsmentioning
confidence: 99%
“…Although showing a reduction in leaf growth, the sweet variety Della retains anthocyanin accumulation, even at higher levels than Razinieh. This has to be seen on the background of the higher level of sugar in the shoot of Della [29] compared to Razinieh [26][27][28]. Since sugars accumulate under P i starvation [36], it is straightforward to assume that glycosylation of the phenolic moiety and import to the vacuole are crucial for this pigment response.…”
Section: Phosphorus Starvation Enhances Primary Root Elongation and Inhibits Shoot Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research investigating the accumulation of sucrose in sweet and grain sorghum stems indicated that sucrose accumulation begins with the start of the reproductive phase (Kanbar, Flubacher, et al, 2021; Lingle, 1987). Sorghum accumulates sugar preferentially in the central internodes, whereas the basal internodes accumulate more stem weight (Kanbar, Flubacher, et al, 2021). Compared to the grain types, sweet genotypes double or even triple the sugar concentration in all internodes (Kanbar et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Sorghum accumulates sugar preferentially in the central internodes, whereas the basal internodes accumulate more stem weight (Kanbar, Flubacher, et al, 2021). Compared to the grain types, sweet genotypes double or even triple the sugar concentration in all internodes (Kanbar et al, 2021). Sucrose is the main soluble sugar of sorghum, accompanied by glucose and fructose (Chen et al, 2014; Simeone et al, 2017), which allows inferring sugar content refractometrically (Murray et al, 2009).…”
Section: Introductionmentioning
confidence: 99%